International Review of Hydrobiology - International Review of Hydrobiology (Wiley, 2026)
International Review of Hydrobiology brings together problem-orientated research. In an economically and environmentally changing world; we look for knowledge-driven ideas. The challenges facing marine and freshwater biology are our focus. Our mission is to translate science into policy, allowing us to understand global systems yet act on a regional scale. Interdisciplinary in nature, editors welcome articles that cover all aspects of aquatic ecosystems and biodiversity studies on ecosystem functioning.
FI 0.62
Q3
Keywords: Life Sciences; Freshwater Ecology; Ecología de agua dulce; Acuerdos transformativos; Transformative agreements; Biología marina y de agua dulce; Ecosistémicos acuáticos